Understanding Consumer Purchase Intention in Cloud Gaming: The Role of Perceived Risk, Ease of Use, and Trust - Suryono, Herdiansyah Gustira Pramudia; Saifullah, Akhsan (The International Journal of Business Review (The Jobs Review), 2024)
Purpose— This study aims to examine the influence of perceived ease of use, perceived risk, and consumer trust on purchase intention in cloud gaming services, specifically in the Indonesian market. As cloud gaming continues to evolve, understanding consumer behavior in this sector is essential for improving service adoption and market penetration.Design/methods/approach–This research employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze relationships among variables. Data were collected from cloud gaming users and processed using SmartPLS 3.3.2 to assess direct and indirect effects.Findings–The results indicate that perceived risk has a significant positive effect on purchase intention (β = 0.620, p 0.05), suggesting that consumers are still willing to subscribe despite acknowledging potential risks. Meanwhile, perceived ease of use does not have a significant impact on purchase intention (β = -0.024, p 0.05), indicating that ease of use is not a primary determinant in consumer decision-making. Additionally, consumer trust has a positive but weaker effect (β = 0.278), showing that while trust is relevant, risk perception remains the dominant factor influencing purchase decisions.Research implications/limitations—This study provides practical insights for cloud gaming providers by emphasizing the importance of risk mitigation strategies such as improving network stability, ensuring data security, and enhancing service transparency. However, this research is limited to one cloud gaming platform (Skyegrid), restricting generalizability to other providers. Future studies should explore comparative analyses across multiple cloud gaming services and consider additional variables such as pricing models, content variety, and user engagement strategies.Originality/value–This study contributes to the growing body of knowledge on technology adoption and consumer behavior in digital entertainment services, particularly in the cloud gaming industry. By focusing on the Indonesian market, it provides empirical evidence on how perceived risk, ease of use, and trust shape purchase intention, offering valuable insights for academics, marketers, and business strategists seeking to enhance consumer adoption of cloud gaming services.